The Analysis of Marketing Efficiency of Shrimp (Case Study at Padang Kerta Village, Karangasem Regency and Pering Village, Gianyar Regency) - I Wayan Sudana (Warmadewa University Press, 2019)
This study aims to determine the pattern of Galah shrimp marketing channels, the number of margins, farmer share and R/c Ratio of marketing institutions in each region. Source of data used are primary data and secondary data collected by interview and documentation methods and then analyzed descriptively with a quantitative approach. The results showed that the price of giant prawns at the producer level was determined by the uniformity and size of the harvest. The more uniform and the bigger the size of giant prawns which are harvested at the higher price. The marketing of giant prawns in the Karangasem and Gianyar regions uses the same marketing channel pattern, from producers to collectors and then to consumers (hotels, restaurants, restaurants), but the marketing margins are different. Galah shrimp marketing margins for the Gianyar region with a margin of 23.90% while in the Karangasem region the percentage of marketing margins is 22.80% while the percentage of farmer shares both in Gianyar and in Karangasem is greater than the percentage of marketing margins in both regions. In Gianyar, the farmer share is 76.04% and in the Karangasem region is 80.07%. The efforts to enlarge Galah prawns carried out in both regions have benefited farmers, where the R / c ratio for producer levels in Gianyar and Karangasem are 1.3 and 2.1 respectively. And based on the calculation of the marketing efficiency of giant prawns in the Gianyar and Karangasem regions, the marketing efficiency of 10.60% and 11.50% respectively. Therefore, the marketing of giant prawns based on the results of this study is classified as efficient.